"Somos Más": Towards a Feminist Critique of the Photographic Archive of the Women's And Feminist Movement Against the Chilean Dictatorship. Issue 4 (2nd October 2022) - Donoso Macaya, Ángeles
Abstract : This article examines the photographic archive of the women's and feminist movement against the civil-military dictatorship in Chile. This corpus is composed of photographic records disseminated by independent media and in alternative publications edited by organisations of women and feminists. Starting from these records, I interrogate the analytical modalities traditionally adopted by photography criticism in Chile when approaching the relationship between "women" and photography. This reflection is oriented around the theoretical and critical work of Andrea Noble: in particular, Noble's reading of Tina Modotti, in which she interrogates and reconsiders the modes of doing photography criticism. The article proposes that the photographic archive expands in space and through time, through the reproduction and circulation of similar or repeated images in distinct media. This expansion enables other ways of seeing and enunciating "protest" in public space at the local level. The analysis emphasises the repetitive quality of the images, and highlights the occasional presence of other photographers in the frame, as aspects that allow the spectator to appreciate and considerate how the visual expansion of the women's movement operates in public space.